Prevention and treatment of catheter-related venous thrombosis in long-term parenteral nutrition: A SINuC position statement - Zaccone, Vincenzo; Santoro, Luca; Guerrieri, Emanuele; Diblasi, Ilaria; Roncarati, Ilaria; Viticchi, Giovanna; Vecchiarelli, Pietro; Santoliquido, Angelo; Fiore, Francesca; Molfino, Alessio; Landi, Francesco; Moroncini, Gianluca; et al. (Frontiers in Nutrition, 2023)
The implementation of long-term parenteral nutrition (PN) often requires the placement of central venous access, a procedure that carries a considerable risk of catheter-related venous thrombosis (CRT). The occurrence of CRT is a severe event in the natural history of patients in PN since it can lead to central venous access loss and PN failure. Despite the importance of this topic in clinical nutrition, the prevention and treatment of CRT in PN represents one of the "gray areas" of the literature for the presence of few randomized controlled clinical trials and the generally low level of evidence in published scientific papers. Through a narrative review of the literature, the Italian Society of Clinical Nutrition and Metabolism (SINuC) aimed to collect some practical recommendations regarding the current state-of-the-art in the prevention, diagnosis, and treatment of CRT in patients undergoing long-term PN.